Kontribusi Regulasi Emosi terhadap Tingkat Stres pada Siswa - Nada Fristy Yusri; Reggiana Brescia; Deasy Dwi Cahayaningtyas Arifin; Farouq Fathurrahman; Risma Kumara Rani (JURNAL BIMBINGAN DAN KONSELING AR-RAHMAN, 2026)
The increasing academic and psychosocial pressures experienced by junior high school students highlight the importance of understanding factors that influence stress levels, particularly emotional regulation. This study aimed to identify the levels of emotional regulation and stress among students at SMPN 243 Jakarta and examine the role of emotional regulation in predicting students’ stress levels. A quantitative correlational design was employed involving 133 students selected through purposive sampling. Data were analyzed using normality and linearity tests, followed by Pearson correlation and simple linear regression analyses. The results revealed that emotional regulation had a significant effect on students’ stress levels (p < .001). The regression equation obtained was Y = 121.606 − 0.481X, with a standardized beta coefficient of β = −0.391. These findings indicate a negative relationship between emotional regulation and stress, suggesting that students with better emotional regulation tend to experience lower levels of stress. Emotional regulation accounted for 15.3% of the variance in students’ stress levels, while the remaining variance was explained by other factors not examined in this study. The findings emphasize the importance of implementing social-emotional learning programs, stress management training, and preventive counseling services to strengthen students’ emotional regulation skills and help them cope more effectively with academic and psychosocial demands. _____________________________________________________________Tekanan akademik dan psikososial yang semakin meningkat pada siswa sekolah menengah pertama menjadikan pemahaman mengenai faktor-faktor yang memengaruhi tingkat stres, khususnya regulasi emosi, semakin penting. Penelitian ini bertujuan untuk mengetahui tingkat regulasi emosi dan stres siswa SMPN 243 Jakarta serta menguji peran regulasi emosi dalam memprediksi tingkat stres siswa. Penelitian menggunakan desain kuantitatif korelasional dengan melibatkan 133 siswa yang dipilih melalui teknik purposive sampling. Data dianalisis menggunakan uji normalitas, uji linearitas, korelasi Pearson, dan regresi linear sederhana. Hasil penelitian menunjukkan bahwa regulasi emosi berpengaruh signifikan terhadap tingkat stres siswa (p < 0,001). Persamaan regresi yang diperoleh adalah Y = 121,606 − 0,481X dengan koefisien beta terstandarisasi sebesar β = −0,391. Temuan ini menunjukkan adanya hubungan negatif antara regulasi emosi dan stres, yang berarti siswa dengan kemampuan regulasi emosi yang lebih baik cenderung mengalami tingkat stres yang lebih rendah. Regulasi emosi memberikan kontribusi sebesar 15,3% terhadap variasi tingkat stres siswa, sedangkan sisanya dipengaruhi oleh faktor lain yang tidak diteliti. Hasil penelitian menegaskan pentingnya pengembangan program pembelajaran sosial-emosional, pelatihan manajemen stres, dan layanan konseling preventif untuk memperkuat kemampuan regulasi emosi siswa dalam menghadapi tuntutan akademik dan psikososial.